Boron neutron capture therapy – a brief review of principles and clinical applications - Krakowiak, Wiktoria E.; Wójciuk, Karolina; Dorosz, Michał; Płódowska, Magdalena A.; Pasińska, Kinga; Węgierek-Ciuk, Aneta; Lankoff, Anna; Wojcik, Andrzej; Lisowska, Halina (Medical Studies/Studia Medyczne, 2026)
Boron neutron capture therapy (BNCT) exploits alpha and lithium particles produced in the boron-10 fission reaction (10B(n,)7Li) with epithermal neutrons to inactivate cancer cells in the tumour volume ranges of produced alpha and lithium particles are limited to individual cells, so the boron-10 atoms should be located only in the target cancer cells. First, there is a need to administer to the patient the boron-10 carrier, which selectively deposits boron-10 atoms in cancer cells. Next, an external beam of epithermal neutrons must be delivered to the treated volume. BNCT is thus a bimodal method, combining epithermal neutron beam teletherapy with systemic therapy. Although BNCT is still under development, recent advances in boron-10 delivery agents and in accelerator-based epithermal neutron beam generation offer a new perspective for BNCT. These advances and some clinical applications of BNCT are briefly reviewed.